Sukses versus Gagal: Pilihan di antara Proses dan Protes - Hotma Enzelina Saragih; Masduki Asbari; Anisa Agustiana; Aina Winda Mareta; Siti Indah Nurcahyani (Journal of Information Systems and Management (JISMA), 2024)
This journal aims to emphasize the importance of process in every effort to achieve success rather than many useless protests and also aims to understand and practice further regarding viewing methods. This journal uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from Helmy Yahya's YouTube channel entitled "Successful people have more processes, unsuccessful people have more protests". From this topic it is about the importance of enjoying every process that each individual goes through and not protesting or complaining too much. To be successful requires a process, there is no instant success. However, don't just focus on what you want to achieve, but also try to enjoy every process that occurs on the way to achieving it. Having clear goals is a good thing, but enjoying every process of achieving them is more important. If you want to only focus on the goal without enjoying every part of the journey then everyone who embarks on it will easily become discouraged, disappointed or even change the direction of the goal that may have been set from the start. The results of this study explain that any success achieved requires a process that is not easy, it requires struggle, hard work, failure and enthusiastic effort.